2011
DOI: 10.1111/j.1365-2826.2011.02157.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nuclear Factor-Kappa B Sensitises Anterior Pituitary Cells to Tumour Necrosis Factor-α- and Lipopolysaccharide-Induced Apoptosis

Abstract: Nuclear factor-kappa B (NF-κB), an important pro-inflammatory factor, is a crucial regulator of cell survival. Both lipopolysaccharide (LPS) and tumour necrosis factor (TNF)-α activate NF-κB signalling. Oestrogens were shown to suppress NF-κB activation. Oestrogens exert a sensitising action to pro-apoptotic stimuli such as LPS and TNF-α in anterior pituitary cells. In the present study, we show by western blotting that 17β-oestradiol (E(2)) decreases TNF-α-induced NF-κB/p65 and p50 nuclear translocation in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…In normal pituitary cells, oestrogens inhibit the NF‐κB pathway, probably by controlling NF‐κB intracellular localisation as reported for other cell types . Indeed, we previously reported that ER activation blocks LPS‐ and TNF‐α‐induced nuclear translocation of NF‐κB/p65 and p50 . In the present study, we found that oestrogens have the opposite effect in GH3 cells because they increased nuclear levels of NF‐κB/105, p65 and p50.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In normal pituitary cells, oestrogens inhibit the NF‐κB pathway, probably by controlling NF‐κB intracellular localisation as reported for other cell types . Indeed, we previously reported that ER activation blocks LPS‐ and TNF‐α‐induced nuclear translocation of NF‐κB/p65 and p50 . In the present study, we found that oestrogens have the opposite effect in GH3 cells because they increased nuclear levels of NF‐κB/105, p65 and p50.…”
Section: Discussionsupporting
confidence: 83%
“…We previously reported that, in normal anterior pituitary cells, E 2 decreases TNF‐α‐induced NF‐κB nuclear translocation and reduces Bcl‐xL expression, an anti‐apoptotic protein target for this transcriptional factor . To evaluate whether oestrogens also modulate NF‐κB activity in pituitary tumour cells, we examined the effect of E 2 on basal and TNF‐α‐induced nuclear translocation of NF‐κB and on Bcl‐xL expression in GH3 pituitary tumour cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies showed that pre-treatment with oestradiol was able to prevent neuronal death by inhibiting the activation of p38 MAPK after the treatment of cells with Aβ (Valles et al 2008). Eijo et al (2011) described that oestradiol was able to decrease TNFα-induced, NFκB p65 and p50 nuclear translocation in primary cultures of anterior pituitary cells from ovariectomized rats. Inhibition of NFκB by melatonin has been also previously reported in other experimental models that showed how melatonin prevented NFκB activation by oxidative stress (Veneroso et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, to elucidate whether PRL proapoptotic effect requires STAT5 regulation of Bcl-2 family proteins, we determined the level of expression of two members of this family that we have previously shown to be regulators of anterior pituitary cells apoptosis, i.e. antiapoptotic Bcl-2 and proapoptotic Bax [28, 49, 50]. PRLR antagonist decreased Bax and increased Bcl-2 expression levels, further supporting the idea that PRLR activation promotes a proapoptotic phenotype in GH3 cells.…”
Section: Discussionmentioning
confidence: 99%